The use of Digital Communication and Information Technologies (DCITs) as a process of knowledge construction and pedagogical innovation within the school environment (Research, Society and Development, 2023)
New technologies and the globalization of process automation configure a scenario of changes that are not only economic, but also social and professional. In this context of global transformations, new professions emerge, while others disappear or are modified by the use of technology. Society today is more dependent on new Digital Communication and Information Technologies (TDCIs) that are present in all scenarios of the globalized world. Given this, the school cannot be absent and resistant to these transmutations that are happening all the time in a unique way and with no return. The use of TDCIs in education has direct results both for the teacher in terms of their pedagogical practice, and for the student in the process of building their knowledge. The aim of the work was to analyze the importance of using TDCIs as a construction of knowledge, as well as promoting an innovation process within the school environment. The article in question was methodologically based on exploratory and descriptive research, in which we sought to gather information about the subject matter. We seek to highlight the use of TDCIs as a process of change in different learning environments and which brings something innovative within it.